KEPATUHAN MINUM OBAT PADA PENDERITA HIPERTENSI YANG BEROBAT KE BALAI PENGOBATAN YAYASAN PELAYANAN KASIH A DAN A RAHMAT WAINGAPU - ULY AGUSTINE; IVONSIANI NATALIA MBAKURAWANG (Poltekkes Kemenkes Kupang, 2016)
Introduction: Hypertension is a disease or disorder of the circulatory system that causes a rise in blood pressure above the normal value. Obedience comes from obedient basic words which means discipline and obedience. The purpose of this study is to identify the relationship between several variables that affect the level of adherence such as age, gender, education, knowledge, occupation, distance perception, severity and range of drug delivery. Method: This research is a quantitative research with nonrandom sampling of sam-pling type purposive sampling. Instrument used in this research in the form of questionnaires and observation sheets involving 30 people respondents suffering from hypertension. Results: Result: The results showed that of 30 respondents studied there were 17 respondents (57%) who did not adhere to taking medicine and there were 13 respondents (43%) who obediently took antihypertensive drugs. Based on Chi-square analysis with 5% significance level found that there is no meaningful relationship between age, sex, education, knowledge, occupation, distance perception, severity, and drug delivery range with medication adherence level Antihypertensive. Suggestion: It is recommended to health officers at BP YPK A and A Rahmat Waingapu to provide health education in the form of counseling about hypertension and its treatment periodically.